Strategies In Teaching Speaking To English Department StudentsAt Muhammadiyah University Of Surakarta - Praja, Abdillah Lila Nata, Aryati Prasetyarini, M.Pd, Dra. Dwi Haryanti, M.Hum (2013)
The objective of this research is to describe the strategies used by the lecturer in teaching Speaking 3 to 3rd semester of English department student. The subject of this descriptive research is the English lecturer and the 3rd Semester students of English department in Muhammadiyah University of Surakarta 2012-2013 academic year. The researcher uses descriptive qualitative research. There are two types of data; primary and secondary. The primary data are taken from the first resources through the direct observation, while the secondary data are taken from the second resources that can be document. The writer collects the data of this research from teaching learning process, interview with the lecturer, interview with the students, document, and observation.In the analyzing data, the researcher employs descriptive qualitative analysis. The analysis started by data reduction then data display and the last step is conclusion drawing. The results of this research show that are: (1) the method used is active learning and the strategy implemented is debate. (2)The problems faced by the lecturer are class management and class facilities. (3)The problems faced by the students are monotonous learning strategies and limited number of words and pronunciations. (4)The problems solution used by the lecturer are using the group and using LCD. In solving problem related to the vocabulary and pronunciation problem, the lecturer gives correction directly and use repetition.